2018
DOI: 10.15640/jmpp.v6n2a2
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Styles and Personality Traits as Predictors of Job Embeddedness among Employees of Ibadan Electricity Distribution Company, Nigeria

Abstract: The incessant change in ownership status of what was formerly known as National Electrical Power Authority (NEPA) and owned by government, but now being controlled by private company has given rise to the need for examining work attitude of employee who were retained in the service. The study, therefore, examined the extent to which leadership styles and personality traits independently and jointly predict job embeddedness of employees. This was with a view to determining factors that could predict job embedde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 14 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…Organizational related forces are known as on-the-job forces, while those that are community-based are called offthe-job factors. On-the-job-embeddedness refers to how attached the employee is to an organization, while off-the-job-embeddedness refers to how connected the employee is to the general community where the firm is situated (Oladeji and Ayinde, 2018). This study, however, focusses on on-the-job factors as it has been found to be responsible to predict factors that will make an employee stay than do off-the-job factors.…”
Section: Job Embeddednessmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational related forces are known as on-the-job forces, while those that are community-based are called offthe-job factors. On-the-job-embeddedness refers to how attached the employee is to an organization, while off-the-job-embeddedness refers to how connected the employee is to the general community where the firm is situated (Oladeji and Ayinde, 2018). This study, however, focusses on on-the-job factors as it has been found to be responsible to predict factors that will make an employee stay than do off-the-job factors.…”
Section: Job Embeddednessmentioning
confidence: 99%
“…These things could be categorized into financial and non-financial, physical or psychological as the case may be. Oladeji and Ayinde (2018) state that sacrifice has to do with the perceived cost of financial or psychological interests that may be lost when an employee leaves his job. To Holtom et al (2006), what could be lost by a departing employee could be both financial and social.…”
Section: Sacrificementioning
confidence: 99%
“…Self-determination theory argues that the extent to which support for psychological needs fulfillment can induce motivation varies among individuals (Deci and Ryan, 2000, 2002). Building on self-determination theory, we argue that employee neuroticism, which is defined as a continual level of emotional adjustment or emotional instability (McCrae and Costa, 1997; Oladeji and Ayinde, 2018), may strengthen leader’s humor influence on HP and the mediating effect of HP between leader humor and employee service outcomes. Research on neuroticism indicates that highly neurotic employees tend to perceive more negative emotions that may reduce their control over work and threaten their need for autonomy (Lanaj et al , 2016; Oladeji and Ayinde, 2018; Young et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Building on self-determination theory, we argue that employee neuroticism, which is defined as a continual level of emotional adjustment or emotional instability (McCrae and Costa, 1997; Oladeji and Ayinde, 2018), may strengthen leader’s humor influence on HP and the mediating effect of HP between leader humor and employee service outcomes. Research on neuroticism indicates that highly neurotic employees tend to perceive more negative emotions that may reduce their control over work and threaten their need for autonomy (Lanaj et al , 2016; Oladeji and Ayinde, 2018; Young et al , 2018). Moreover, to relieve their negative emotions, highly neurotic employees often require more social support and thus have a stronger need for relatedness (Oladeji and Ayinde, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation